Housing Market Constraints in the West African Region - Oyalowo, Basirat A. (Mediterranean Journal of Social Sciences, 2012)
This study examines the constraints limiting lending institutions’ participation in housing finance supply in the WestAfrican region. It also recommends actions necessary for addressing these constraints. It is based on regression analysis ofsecondary data related to factors necessary for lending institutions’ participation in formal housing finance supply. The ratio ofthe private credit to GDP of West African countries between 2008 and 2010 is regressed against the independent variablesInflation rate, procedures to register property, time to register property, cost to register property, strength of legal right index anddepth of credit information system. The private to credit ratio is used as a proxy for the mortgage to GDP ratio due to lack ofaccess to data for most of the West African countries. The regression analysis showed that two factors: ‘depth of creditinformation system’ and ‘strength of legal right index’ are statistically significant to explain the lack of depth of the private credit toGDP ratios in the region. It is concluded that the housing market across several West African countries could be strengthened ifthe governments act to substantially improve the legal strength of lenders is increased through stronger foreclosure laws, andwhere lenders can effectively access, collect, share and disseminate credit information on prospective borrowers in the region.This can be addressed by setting up institutions to convert credit information from informal thrift and savings societies which areactive in the region, to formal private and public credit bureaus.